Hypertrophic Phenotypic Cardiomyopathy in an Ocelot (Leopardus pardalis) - Nascimento Farsette, Anna Beathriz; Alberigi, Bruno; do Vale Aben-Athar, Carolina; da Silva Paulino, Jessica; Trindade Alves, Arthur Carlos; de Almeida Barros, Matheus; Das Neves Dias Neto, Ramiro (Acta Scientiae Veterinariae, 2023)
Background: Hypertrophic cardiomyopathy phenotype (HCM) is the most common cardiac disease in domestic cats but is rarely described in wild species. This phenotype is characterized by concentric hypertrophy of the left ventricle and may be of familial inheritance or secondary to other diseases such as hyperthyroidism, chronic kidney disease, systemic arterial hypertension, and hyperaldosteronism. HCM can cause diastolic and systolic dysfunction and may cause congestive heart failure in affected animals. The present work aims to describe the first report of cardiomyopathy of the hypertrophic phenotype in a specimen of Leopardus pardalis, kept under human care. Case: A 11-year-old female ocelot (Leopardus pardalis) kept under human care, during a preventive care visit, had hypertrophic cardiomyopathy phenotype detected by cardiological evaluation with echocardiogram and a murmur grade III/VI could be detected on cardiac auscultation. This preventive care occurred under chemical restraint with ketamine [6 mg/kg, i.m] associates with midazolam [0.5 mg/kg, i.m] and other evaluations have been done like complete blood count (CBC), biochemistry (alanine aminotransferase, aspartate aminotransferase, total proteins, albumin, albumin:globulin ratio, creatinine, urea, sodium, potassium, calcium, phosphorus, and globulin) and tyroid hormones [free tyroxine (T4) and thyroid-stimulating hormone (TSH)]. Medical management based on clopidogrel, and atenolol was administered for 3 months until the patient showed manifestations of congestive heart failure (CHF) 80 days later the initial evaluation. In this moment the patient presented with dyspnea, so a cardiological and laboratory evaluation was requested. On pulmonary auscultation crackling was identified, suggesting pulmonary edema and, on echocardiographic examination, some parameters had worsened. The CBC and biochemistry were all within reference ranges. Then, the beta-blocker was discontinued and replaced by pimobendan combined with furosemide as treatment of CHF, and the condition stabilized. After one year, the patient was re-evaluated and showed a slight improvement in the condition but still remained stable. Also, feline proBNP levels was tested (SNAP Feline proBNP® IDEXX) in this moment and it was increased. Discussion: The findings on echocardiography associated with the subjective evaluation associated with progressive worsening and clinical manifestation of CHF, as well as the response to treatment, even though there are no reference values for the species, reinforce the diagnosis. There is no evidence to suggest diseases that may contribute to secondary left ventricular hypertrophy. It is believed that pimobendan plays a key role in maintaining hemodynamic balance, since this has already been observed in other mammalian species. The use of beta blockers is commonly employed in domestic cats with HCM, and they have been prescribed in an attempt to promote greater ventricular relaxation, decrease left ventricular outflow obstruction, thus improving ventricular filling for maintenance of cardiac output. In view of the atrial enlargement and possible risk of thrombus formation, clopidogrel was prescribed, extrapolating what is known from domestic cats. It is reasonable to conclude that in this case, the cardiomyopathy behaved similarly to what is observed in domestic cats, both in its clinical evolution and in the means of diagnosis, and in its response to the therapy instituted. Keywords: Felidae, feline, cardiovascular disease, heart disease, echocardiogram, echocardiography.